2012
DOI: 10.1007/s10162-012-0313-8
|View full text |Cite
|
Sign up to set email alerts
|

Memory T Cells in the Chronic Inflammatory Microenvironment of Nasal Polyposis are Hyporesponsive to Signaling Through the T Cell Receptor

Abstract: A majority of T cells from chronic inflammatory tissues derived from patients with nasal polyposis were found to express an effector memory phenotype. We report here that these memory T cells failed to activate NF-κB in response to TCR stimulation but responded normally when the proximal TCR signaling molecules were bypassed with PMA and ionomycin. The dysfunction of these cells was associated with a decrease in the phosphorylation of several TCR proximal signaling molecules including ZAP70, Lck and SLP-76. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 43 publications
1
7
0
Order By: Relevance
“…Subsequent studies showed that the CD3+ T cells in polyps are predominantly CD8+ with a minority of CD4+ T cells (Bernstein et al, 2004;Ickrath et al, 2017), and that the majority of these CD8+ T cells express CD44, CD45RO, CD28, and CXCR3 and are negative for CD62L and CD25 (Baba et al, 2015;Lehman et al, 2012;Pant et al, 2013;Sanchez-Segura et al, 1998). This phenotype is consistent with that of T cells called effector memory T cells, (T EM ) (Sallusto et al, 1999).…”
Section: Introductionmentioning
confidence: 55%
See 3 more Smart Citations
“…Subsequent studies showed that the CD3+ T cells in polyps are predominantly CD8+ with a minority of CD4+ T cells (Bernstein et al, 2004;Ickrath et al, 2017), and that the majority of these CD8+ T cells express CD44, CD45RO, CD28, and CXCR3 and are negative for CD62L and CD25 (Baba et al, 2015;Lehman et al, 2012;Pant et al, 2013;Sanchez-Segura et al, 1998). This phenotype is consistent with that of T cells called effector memory T cells, (T EM ) (Sallusto et al, 1999).…”
Section: Introductionmentioning
confidence: 55%
“…However, when T-cells derived from nasal polyps were tested for their response to activation via the T-cell receptor, it was established that both CD4+ and CD8+ T-cells were profoundly hypo-responsive to an activation stimulus (Lehman et al, 2012). These T-cells had a phenotype of effector memory cells and their anergy was manifested by a blockade in the activation signaling cascade before or just after diacylglycerol (Lehman et al, 2012).…”
Section: Histopathology and Immunohistochemistry Of Nasal Polyp Tissuesmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, as the VAT environment is hypoxic and rich in FFA, it promotes the activation of VAT-infiltrating macrophages via the HIF-1α and TLR4 signalling pathways, leading to the production of TNFα and further establishing a pro-inflammatory environment [35][36][37][38]. These multiple factors could work in concert to overwhelm the anti-inflammatory cytokines and environment produced by TH2 CD4 T cells, iNKT and Treg cells [39][40][41][42][43][44][45].…”
Section: Low-grade Chronic Inflammation and A Dysregulated Immune System: Similarities Between Obesity And Agingmentioning
confidence: 99%